Case study of Oriental Medicine Treatment with Mae-sun therapy of the spinal cord injury due to lumbar burst fracture - Kwon Gi-sun; Park Jung-ah; Noh Ju-hwan; Kim Cheol-hong (Korean Pharmacopuncture Institute, 2010)
Objective : Traumatic lumbar burst fracture causes significant spinal cord injury. This report is intended to estimate the efficacy using oriental treatment on a patient with lumbar burst fracture and spinal cord injury. Methods : From 21th December, 2009 to 5th February, 2010, 1 female inpatient diagnosed with lumbar burst fracture and spinal cord injury was treated with general oriental medicine therapy : mae-sun therapy ; acupuncture ; moxibustion ; pharmacopuncture ; physical therapy and herbal medication. TUG, SCIMⅡ and VAS were used for evaluation of gait disturbance and pain in both feet. Measurement of self voiding amount and remaining amount through CIC was used for evaluation of neurogenic vesical dysfunction. Results : The patient showed a certain degree of improvement in gait disturbance, pain in both feet and neurogenic vesical dysfunction through above evaluation methods. Conclusion : Oriental treatments such as mae-sun therapy, acupuncture and moxibustion therapy, pharmacopuncture therapy and herbal medication can be effective for spinal cord injury due to traumatic lumbar burst fracture.